Porosity Changes in a Metal–Organic Framework HKUST‐1 by Controlled Hydrolysis. (13th April 2016) - Choi, Sang Beom; Sim, Jaeung; Park, Hye Jeong; Kang, Eunyoung; Jung, Soon Gil; Kim, Jaheon
Abstract :